《姚拓与《蕉风》（1955-1963）的反共论述》= Yiu Hong and the anti-communist discourse of Chao Foon (1955-1963) - 杨哲欣 Yang, Ze Xun (Nanyang Technological University, 2021)
友联出版社在亚洲基金会的资助下成功出版了一份“纯文艺刊物”——《蕉风》，它与其姐妹刊物《学生周报》成为了美方在东南亚文化冷战场域中反共的喉舌之一。然而，由于《蕉风》在宗旨、营销上的特殊性，导致它与《学生周报》在反共工作上的处理有所不同。本文中使用了亚洲基金会档案的第一手文献，通过整理和分析档案证明《蕉风》的确有得到美方幕后资助。姚拓作为友联的《蕉风》总编辑、友联出版社董事成员之一，他曾在《蕉风》上发表过很多文章，在第一部分中，笔者将从这些文章中对《蕉风》和姚拓在《蕉风》上的文章找出反共的线索、反共的叙述与政治立场进行研究；在第二部分，笔者将探讨《蕉风》与姚拓对马华文坛的影响与贡献。With funding from the Asia Foundation, Union Publishing has successfully published a "pure literary publication"-Chao Foon. It and its sister publication "Student Weekly" have become the representative of the US anti-communist in the field of culture cold war in Southeast Asian. However, due to the special purpose and marketing of Chao Foon, its handling of anti-communist work is different from "Student Weekly". This article uses the first-hand literature from the archives of the Asia Foundation, and the sorting and analysis of the archives prove that Chao Foonis indeed funded by the United States behind the scenes.Yiu Hong, as the editor-in-chief of Chao Foon andthe director of Union Press, hadpublished many novels in the column of Chao Foon.In the first part, the author will find out anti-communist clues, anti-communist discourseand political stances from these articles on Chao Foonand Yiu Hong's articles on Chao Foon.In the second part, the author will discuss the influence and contribution of Chao Foonand Yiu Hongto the Malaysian Chinese literary world.